2014
DOI: 10.2355/isijinternational.54.165
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Rolling Chatter Model Considering Unsteady Lubrication

Abstract: Chatter, limiting the rolling speed for thin steel strips, has been identified as a serious limitation in increasing the efficiency of the cold rolling process. Many experimental investigations have led to the point that lubrication is one of the effective factors causing chatter. In this article, a new chatter model of the cold strip rolling with consideration of unsteady lubrication is proposed. The limiting shear stress concept and the variation of the lubricant viscosity with pressure are considered in thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…This can be expressed by the fact that during vibrations, the pressure distribution within the roll bite is changed and the Coulomb model can better reflect this issue. Also the friction stress in practice usually exceeds the lubricant limiting shear stress 20) and in the other hand, the amount of lubricant limiting shear stress is a function of the lubricant pressure. 28) In the following, as one of the most effective and controllable process parameters, the effect of friction on chatter in tandem mills is examined.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…This can be expressed by the fact that during vibrations, the pressure distribution within the roll bite is changed and the Coulomb model can better reflect this issue. Also the friction stress in practice usually exceeds the lubricant limiting shear stress 20) and in the other hand, the amount of lubricant limiting shear stress is a function of the lubricant pressure. 28) In the following, as one of the most effective and controllable process parameters, the effect of friction on chatter in tandem mills is examined.…”
Section: Resultsmentioning
confidence: 99%
“…(6) and (8) The force balance equation in the x-axis can be expressed by the slab element. 20) ................ (10) In the above equation, if position x is larger than the neutral point position, xn, the minus sign is used, otherwise the plus sign should be used. Assuming that the rolling pressure, p, and the strip tensile stress, σx, are the principal stresses, it is concluded that σy = -p and with the yield criterion under the plane strain conditions (σx -σy = σk), Eq.…”
Section: Rolling Process Modelmentioning
confidence: 99%
See 3 more Smart Citations